An ever-closer union? Measuring the expansion and ideological content of European Union policy-making through an expert survey. (December 2017) - Nanou, Kyriaki; Zapryanova, Galina; Toth, Fanni
Only a few studies have measured the expansion of European Union competences and they have relied on information derived from consecutive treaties, producing measures that do not vary in between. But decisions on the allocation of authority to the European Union also occur regularly through secondary legislation. This article presents a new index of the Europeanisation of policy based on an expert survey. The index provides a valuable new resource, encompassing 1957 to 2014, on the distribution of authority between the European Union and member states across policy fields, and on the ideological content of primary and secondary legislation. The study discusses the contributions made to existing scholarship, presents key findings from experts' assessments, and demonstrates how the dataset can advance research on European integration.